Digitalisasi Acara Pekan Ilmiah Tahunan IDI Kuningan Melalui Implementasi WordPress dan Elementor - Aan Ansori; Paula Dewanti (Progresif: Jurnal Ilmiah Komputer, 2025)
This study examines the implementation of a website based on the Content Management System (CMS) WordPress to support the organization of the Annual Scientific Meeting (PIT) of the Indonesian Medical Association (IDI) Kuningan Branch. The primary objective of this project is to address various challenges in event management, which is still conducted manually, such as decentralized information and unstructured participant handling processes. The developed website is designed as an integrated platform for information dissemination and participant registration, aiming to improve the efficiency of event execution. The website development follows the Waterfall methodology, utilizing WordPress as the primary CMS, supported by the Elementor plugin for interface customization and Midtrans for online payment systems. Evaluation results indicate that the website implementation is effective for managing large-scale scientific events. Based on trials with 10 users, a high level of satisfaction was observed in terms of ease of use, information delivery, and payment processes.Keywords: Digital Business; Content Management System; Elementor; Indonesian Medical Association; Website AbstrakPenelitian ini mengkaji implementasi website berbasis Content Management System (CMS) WordPress untuk mendukung penyelenggaraan Pekan Ilmiah Tahunan (PIT) Ikatan Dokter Indonesia (IDI) Cabang Kuningan. Tujuan utama dari proyek ini adalah mengatasi berbagai kendala dalam pengelolaan acara yang masih dilakukan secara manual, seperti informasi yang tidak terpusat dan proses penanganan peserta yang kurang terstruktur. Website yang dikembangkan dirancang sebagai platform terpadu untuk penyebaran informasi dan pendaftaran peserta, sehingga diharapkan dapat meningkatkan efisiensi dalam pelaksanaan acara. Pengembangan website mengikuti Metode Waterfall, menggunakan WordPress sebagai CMS utama, dilengkapi plugin Elementor untuk kustomisasi antarmuka dan Midtrans untuk mendukung sistem pembayaran daring. Hasil evaluasi menunjukkan bahwa implementasi website ini efektif untuk pengelolaan acara ilmiah berskala besar. Berdasarkan uji coba terhadap 10 pengguna, ditemukan tingkat kepuasan yang tinggi dalam hal kemudahan penggunaan, penyampaian informasi, dan proses pembayaran.Kata Kunci: Bisnis Digital; Content Management System; Elementor; Indonesian Medical Association; Website